A theoretical analysis of independent business owners' preferences for informal information sources. Issue 1 (22nd October 2020) - Chan, Joel; Brier, Jonathan; Farhadi, Zahra; Lee, Myeong; Janzen, Shawn; Chi, Wei‐Wei; Fellows, Andrew; Winter, Susan
Abstract: Independent business owners often prefer informal information sources to formal ones such as library collections. Part of these preferences is rational because contextual and application‐oriented information is usually available from informal sources, which are theoretically the best matches for this kind of information. This suggests that, in addition to outreach strategies, efforts to integrate informal sources of business‐relevant information can improve public libraries' ability to support independent business owners' information needs. Through interviews with business information providers and users, we explore the multi‐dimensional space of information needs in independent businesses.